Collaboration among psychological researchers, the government, and non-profit organizations for “Konkatsu” (marriage hunting) in Japan - Nishimura, Takashi; Souma, Toshihiko; Kito, Mie; Taniguchi, Junichi; Kanemasa, Yuji; Yamada, Junko; Miyagawa, Yuki (Frontiers in Psychology, 2022)
In contemporary Japanese society, it is difficult to find a marriage partner, and therefore, “Konkatsu,” the search for a marriage partner, has become a socially accepted activity in Japan. In response to this social challenge, in addition to private companies, governments and non-profit organizations are supporting individuals in their search for a marriage partner. This paper reviews statistical information related to marriage hunting published in Japan. In addition, some of the authors’ collaborative activities and academic publications based on these activities are reviewed. Subsequently, the paper discusses and highlights the importance of helping individuals have confidence in their physical attractiveness.